A rotational encoder based hesitance exchanging engine control approach - Mr. V.Saidulu ,; Mr. N.Mahesh ,; Dr. K.Suneeta , (The journal of contemporary issues in business and government, 2017)
Switched Reluctance Motors (SRMs) are becoming more popular in electric drive development due to their advantages and environmental concerns. In terms of development, the SRM has a prominent position because to its ease of use, robustness and cheap cost. It is possible to use a sensorless approach to operate SRM, however this method is more complicated and has a greater number of limitations. Sensor-based rotor position detection, on the other hand, has several benefits, despite the fact that it requires hardware to be attached to the shaft. According to the findings of this study, digital signal controllers may be used to create a control strategy. A solution to the wide-range speed and stationary operating issues may be found in this approach. On-off times of switches may be adjusted through software as well. Simulators and tests were used to confirm the findings.